Physiological and Proteomic Responses of Contrasting Alfalfa (Medicago sativa L.) Varieties to High Temperature Stress - Li, Yingzhu; Li, Xinrui; Zhang, Jin; Li, Daxu; Yan, Lijun; You, Minghong; Zhang, Jianbo; Lei, Xiong; Chang, Dan; Ji, Xiaofei; An, Jinchan; Li, Mingfeng; et al. (Frontiers in Plant Science, 2021)
High temperature (HT) is an important factor for limiting global plant distribution and agricultural production. As the global temperature continues to rise, it is essential to clarify the physiological and molecular mechanisms of alfalfa responding the high temperature, which will contribute to the improvement of heat resistance in leguminous crops. In this study, the physiological and proteomic responses of two alfalfa (Medicago sativa L.) varieties contrasting in heat tolerance, MS30 (heat-tolerant) and MS37 (heat-sensitive), were comparatively analyzed under the treatments of continuously rising temperatures for 42 days. The results showed that under the HT stress, the photosynthetic system and membrane system of two alfalfa varieties were damaged. However, because the antioxidation-reduction and osmotic adjustment ability of MS30 are significantly stronger than MS37, the damage degree of the photosynthetic system and membrane system of MS30 is significantly lower than that of MS37. On this basis, the global proteomics analysis was undertaken by tandem mass tags (TMT) technique, a total of 6,704 proteins were identified and quantified. Gene Ontology (GO) analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis indicated that a series of key pathways including photosynthesis, metabolism, adjustment and repair was affected by HT stress. Through analyzing Venn diagrams of two alfalfa varieties, 160 and 213 differentially expressed proteins (DEPs) that had dynamic changes under HT stress were identified from MS30 and MS37, respectively. Among these DAPs, we screened out the key DEPs related to photosynthesis, antioxidant, heat shock protein and metabolism, such as ATP-dependent zinc metalloprotease FTSH protein, vitamin K epoxide reductase family protein, ClpB3, etc., which plays important functions in response to HT stress. In conclusion, the stronger heat-tolerance of MS30 was attributed to its higher adjustment and repair ability, which could cause the metabolic process of MS30 is more conducive to maintaining its survival and growth than MS37, especially at the later period of HT stress. This study provides a useful catalog of the Medicago sativa L. proteomes with the insight into its future genetic improvement of heat-resistance.